THE MECHANISM COMPARATIVE LEARNING NATIONAL AND INTERNATIONAL STANDARDS OF EDUCATION - Ruzmetova Novval Vahabdjanovna; Abdirashitova Malika Azimjon qizi (Bright Mind Publishing, 2026)
This article examines the mechanisms of comparative learning between national and international standards of education. The study is based on regulatory frameworks governing the development and implementation of state educational standards in Uzbekistan, as well as internationally recognized educational standards. Through a comparative learning mechanism, the goals, content, structure, and implementation stages of educational standards are analyzed. The findings contribute to aligning national education standards with international requirements and improving the quality of education.
Keywords: National educational standards, International educational standards, Comparative learning mechanism, Improving education quality, Competency-based education, Document analysis method, Structural-functional analysis method, Benchmarking method, Comparative modelling.